Racial disparities in provider-patient communication of incidental medical findings. (May 2021) - Schut, Rebecca A.
Abstract: Health disparities research often focuses on the social patterning of health outcomes. Increasingly, there has been an emphasis on understanding the mechanisms perpetuating disparities, even after issues of patient access to health services are addressed. The following study utilizes a novel dataset of electronic medical records (EMR), radiology records, and U.S. Census data to investigate the racial/ethnic patterning of provider-patient communication among patients diagnosed with incidental medical findings requiring follow-up. My results indicate that racial/ethnic disparities in follow-up adherence stem from initial disparities in provider-patient communication. These communication disparities persist even after accounting for multiple socioeconomic, health, and provider characteristics, indicating a bias in medicine, whereby providers are less likely to communicate information about incidental medical findings to patients of color relative to White patients. This paper has important clinical implications, as it sheds new light on why we might see low adherence to medical advice among patients of color. Findings also have social, political, and policy relevance, as they suggest an important mechanism through which health inequalities persist. To finally eliminate racial/ethnic health inequalities in the United States, racial bias and discrimination within medical and public health infrastructures must be eliminated. Highlights: Examines if disparate provider-patient communication of incidental medical findings occurs. Finds provider-patient communication occurs disparately across patient racial groups. Effects strongest for Hispanic and Black patients; disparities remain after including controls. Access to primary care somewhat attenuates communication disparities. Policies must address provider communication bias and ensure access to primary care.